Caracterización clínica y angiográfica según sexo de pacientes con síndrome coronario agudo sin supradesnivel del segmento ST - Ugalde P., Héctor; Romero A., Pablo; Cifuentes R., Ignacio (Revista Hospital Clínico Universidad de Chile, 2020)
Ischemic Heart Disease is the leading cause of death and of potential years of life lost in Chile. The most frequent acute presentation of this group of pathologies is the Acute Coronary Syndrome (ACS) without ST segment elevation. According to the literature, there is a proportion of patients with non-ST elevated ACS in which coronary angiography reveals a mild coronary lesion or even shows no detectable lesion at all. This scenario is more common in women than in men. Compared with men, women with non-ST elevated ACS are older than men and more frequently have hypertension. Furthermore, women are less likely to have previous cardiac diseases, and are less common to present serum troponin rise at admission. In Chile, there are no previous studies about the differences between sexes in this disease. The objective of this study is to determine if there are major differences between sexes in aspects like clinical and angiographic findings in patients with non-ST elevated ACS. The study used a database of 1900 consecutive patients who were submitted for coronary angiography and had been previously diagnosticated with non-ST elevated ACS, between the years 2001-2017. Clinical assessment, laboratory and angiographic results were collected and analyzed to establish major differences considering p<0,05. 69% of patients were men. When comparing, the proportion of smokers was greater in men, who also more frequently had progressive worsening of angina or treatment-resistant chest pain as clinical presentations. Furthermore, previous coronary bypass surgery, previous percutaneous coronary intervention and previous myocardial infarction were more common in men. As to women, they were older and more frequently had hypertension and/or hypothyroidism. Unstable angina as a clinical presentation was more usual than in men and electrocardiographic findings as a negative T-wave in the anterior wall, evolutive segment changes and left branch bundle block were also more common. In addition, serum troponin rise was more frequent than in men. There was no difference in risk stratification with TIMI score. When comparing angiographic findings, women had more frequently mild lesions or no lesions at all (44% in women versus 27% in men). In conclusion, clinical aspects are different in between sexes as to presence of comorbidities, cardiovascular risk factors and previous cardiovascular disease. Clinical presentation is also different, as to symptoms and as to electrocardiographic findings and laboratory exams. At last, and as evidence suggests, there is a greater proportion of women with mild coronary lesions or without lesions than in men when comparing angiographic findings.